Spin–orbit coupled molecular quantum magnetism realized in inorganic solid - Sang-Youn Park (Nature Portfolio, 2016)
Molecular magnets may provide fundamental building blocks for future spintronic and quantum information technologies. Here, the authors demonstrate how the Yb4 tetrahedral components of inorganic materials Ba3Yb2Zn5O11behave as isolated molecular magnets.